Non-tumoral uptake of 68Ga-FAPI-04 PET: A retrospective study - Qi, Na; Wang, Hao; Wang, Haiyan; Ren, Shuhua; You, Zhiwen; Chen, Xing; Guan, Yihui; Xie, Fang; Hua, Fengchun; Zhao, Jun (Frontiers in Oncology, 2022)
Objective: Fibroblast activation protein (FAP) -targeting radiopharmaceutical based on the FAP-specific inhibitor (FAPI) is considered as a potential alternative agent to FDG for tumor-specific imaging. However, FAP is also expressed in normal adult tissues. The aim of this study was to explore the image features of non-tumoral regions with high uptake of FAPI in PET imaging and to reveal the physiological mechanisms of these regions. Material: One hundred and thirty-seven patients who underwent whole body 68Ga-FAPI PET/MR (n=46) or PET/CT (n=91) were included in this retrospective study. Three experienced nuclear medicine physicians determined the non-tumoral regions according to other imaging information (CT, MRI, 18F-FDG PET or ultrasound), clinical information or pathological results. The regions of interest (ROI) were drawn manually and the maximum standardized uptake value (SUVmax) was measured. Results: A total of 392 non-tumoral uptake regions were included in this study. The included physiological regions were: uterus (n=38), submandibular gland (n=118), nipple (n=37), gingiva (n=65), esophagus (n=31). The incidence of 68Ga-FAPI-04 uptake in physiological regions was independent of age, the tracer uptakes in the gingiva and esophagus were more common in male patients (P=0.006, 0.009), while that in the nipple was more common in female patients (P < 0.001). The included benign regions were: inflammatory lymph node (n =10), pneumonia (n=13), atherosclerosis (n=10), pancreatitis (n=18), osteosclerosis (n=45), surgical scar (n=7). No significant difference was observed in SUVmax between physiological and benign regions. Conclusions: This study evaluated the SUVmax of 68Ga-FAPI-04 in non-tumoral uptake regions with a relatively large sample population. A number of organs exhibit physiological uptakes of 68Ga-FAPI-04. Gender has a more significant effect on physiological expression of FAPI than age. No statistical differences in FAPI uptake were found between benign and physiological high uptake regions. Our study showed that regions with high FAPI uptake did not necessarily represent malignancy. Therefore, being familiar with physiological FAPI uptake and the uptake of typical benign lesions can be very helpful for physicians to interpret images and make a diagnosis.